He2+ Impact Single Ionization Cross Sections of Fe Atom - Gupta, S. P.; Yadav, K.; Khanal, R.; Jha, L. K. (Journal of Nepal Physical Society, 2020)
Binary encounter approximation has been used for theoretical calculations of alpha particle (He2+) impact single ionization cross sections of iron atom at ground state in the energy range of 35 to 360 keV/amu. The cross sections for energy transfer given by Vriens’ and quantum mechanical Hartree-Fock velocity distributions for target electron have been used in the calculation. The contributions in total single ionization cross sections from 4s and 3d subshells are observed to be higher than from 3p, and the contributions from 4s decreases with increase of impact energy whereas the contribution from 3d increases. The total single ionization cross sections decrease gradually with the increase of impact energy similar to experimental results which implies that our results are in satisfactory agreement with the experimental data in the given energy range.